1997
DOI: 10.1108/10662249710171814
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for and barriers to Internet usage: results of a national public opinion survey

Abstract: Analyzes a national random telephone survey, carried out in October 1995, on the motivations for and barriers to Internet usage. Eight percent of the random sample reported being Internet users, while surprisingly another 8 percent reported being former users. In total, 85 percent of respondents reported having heard of the Internet. The survey showed evidence of a digital divide, Internet users being generally wealthier and more highly educated, and blacks and Hispanics disproportionately unaware of the Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
170
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(183 citation statements)
references
References 6 publications
7
170
0
6
Order By: Relevance
“…ISP choice variables measure factors underlying the respondent's choice of ISP. Respondent and household sociodemographic variables considered here are those found to be important in other studies (Katz and Aspden, 1997;Madden and Simpson, 1997;Kridel et al, 1998;Madden and Savage, forthcoming). The list of all variables included in the econometric model is provided in Table 6.…”
Section: Variables and Econometric Modelmentioning
confidence: 95%
“…ISP choice variables measure factors underlying the respondent's choice of ISP. Respondent and household sociodemographic variables considered here are those found to be important in other studies (Katz and Aspden, 1997;Madden and Simpson, 1997;Kridel et al, 1998;Madden and Savage, forthcoming). The list of all variables included in the econometric model is provided in Table 6.…”
Section: Variables and Econometric Modelmentioning
confidence: 95%
“…A variety of studies on information communication technologies (ICT's) have highlighted the importance of informal social networks for new media adoption (Stewart, 2007). Facer, Furlong, Furlong and Sutherland (2001), for example, showed that ICT skills are mainly acquired informally in homes rather than through formal education in schools, and Katz and Aspden (1997) found that most people learned how to use the Internet from family, friends and colleagues. The workplace is a frequently reported location for learning to use computers (Selwyn, Gorard & Furlong, 2006).…”
Section: Sources Of Support As a Factor Explaining Internet Skill Difmentioning
confidence: 99%
“…Digital inequality, in this research, refers to inequality in the access and use of information and communication technologies (DiMaggio et al 2004). Survey studies have indicated that digital inequality exists across a variety of demographic, ethnic, and geographic dimensions (Katz and Aspden 1997;Lenhart 2002;NTIA 1998NTIA , 1999NTIA , 2000NTIA , 2002OECD 2001). Among these dimensions, income and education-which suggest one's socio-economic status-have exhibited the most significant power in distinguishing use or nonuse of information and communication technologies (ICT) (Jung et al 2001;Lenhart 2002).…”
Section: Introductionmentioning
confidence: 99%